2011
DOI: 10.1016/j.neuroscience.2011.07.072
|View full text |Cite
|
Sign up to set email alerts
|

Transgene expression in the striatum following intracerebral injections of DNA nanoparticles encoding for human glial cell line-derived neurotrophic factor

Abstract: A goal of our studies is to develop a potential therapeutic for Parkinson’s disease (PD) by a human GDNF (hGDNF) expression plasmid administered to the rat striatum as a compacted DNA nanoparticle (DNP) and which will generate long-term hGDNF expression at biologically active levels. In the present study we used a DNA plasmid encoding for hGDNF and a polyubiquitin C (UbC) promoter that was previously shown to have activity in both neurons and glia, but primarily in glia. A two-fold improvement was observed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…Consequently, the direct delivery of GDNF to the brain was the primary focus of translational research. Delivery strategies have included the direct administration of the molecule, its encapsulation in microspheres composed of biodegradable polymers to achieve a controlled release over a prolonged period of time, DNA nanoparticle gene transfer, and convection-enhanced delivery [76][77][78][79]. Interactions of GDNF with components of the extracellular matrix ,its activation of receptors other than RET/GFRα1, induction of anti-GDNF antibodies by recombinant GDNF are all factors hampering the use of the full molecule in therapy.…”
Section: Protein Based-therapymentioning
confidence: 99%
“…Consequently, the direct delivery of GDNF to the brain was the primary focus of translational research. Delivery strategies have included the direct administration of the molecule, its encapsulation in microspheres composed of biodegradable polymers to achieve a controlled release over a prolonged period of time, DNA nanoparticle gene transfer, and convection-enhanced delivery [76][77][78][79]. Interactions of GDNF with components of the extracellular matrix ,its activation of receptors other than RET/GFRα1, induction of anti-GDNF antibodies by recombinant GDNF are all factors hampering the use of the full molecule in therapy.…”
Section: Protein Based-therapymentioning
confidence: 99%
“…GDNF plasmid were compacted into DNA NP and injected into the brain achieving a long-term expression in the brain [237].…”
Section: Invasive Methods; Local Administrationmentioning
confidence: 99%
“…This small size allows the transfection of post-mitotic cells and could mediate GDNF transgene expression in the rat striatum for up to three weeks post intrastriatal injection [209]. A follow up study showed that GDNF transgene expression could be observed for up to six months and showed that GDNF levels were higher in the 6-OHDA model than in the healthy brain [210]. Since the 6-OHDA causes a large upregulation of astrocytes in the rat 6-OHDA model [211] it is likely that this increased GDNF level is due to the transfection of astrocytes, being greater in number in the 6-OHDA model than the healthy brain [210].…”
Section: Cynomolgus Monkeymentioning
confidence: 99%
“…A follow up study showed that GDNF transgene expression could be observed for up to six months and showed that GDNF levels were higher in the 6-OHDA model than in the healthy brain [210]. Since the 6-OHDA causes a large upregulation of astrocytes in the rat 6-OHDA model [211] it is likely that this increased GDNF level is due to the transfection of astrocytes, being greater in number in the 6-OHDA model than the healthy brain [210]. A previous study has shown that primary astrocytes extracted from the midbrain of the newborn rat are far less amenable to non-viral transfection than immortalized Neu7 astrocytes [96].…”
Section: Cynomolgus Monkeymentioning
confidence: 99%